2020
DOI: 10.1021/acsabm.0c00064
|View full text |Cite
|
Sign up to set email alerts
|

Xenohybrid Bone Graft Containing Intrinsically Disordered Proteins Shows Enhanced In Vitro Bone Formation

Abstract: Bone defects are a significant health problem worldwide, as bone is the second-most transplanted tissue after blood. Although a myriad of bone grafts (BGs) have been used to treat bone repairs, none of them possesses all the desirable characteristics. An approach to improve BGs is to add bio-active components, however often difficult as BG production may disrupt the biological activities of such molecules. Here, we present a composite xenohybrid BG, SmartBonePep, with a type of biomolecule inspired by intrinsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 60 publications
(107 reference statements)
1
9
0
Order By: Relevance
“…Since OCN is synthesized almost exclusively by highly differentiated osteoblasts (Price et al, 1976;Eastell and Hannon, 2007) Eastell andHannon, 2007Price et al, 1976, these results indicated that the hMSCs on the SBPs were in the process of differentiation to osteoblasts phenotype. The effect on OCN was also seen in a previous study with these materials, when human osteoblasts from a variety of donors were seeded onto SmartBonePep R (Zhu et al, 2020).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Since OCN is synthesized almost exclusively by highly differentiated osteoblasts (Price et al, 1976;Eastell and Hannon, 2007) Eastell andHannon, 2007Price et al, 1976, these results indicated that the hMSCs on the SBPs were in the process of differentiation to osteoblasts phenotype. The effect on OCN was also seen in a previous study with these materials, when human osteoblasts from a variety of donors were seeded onto SmartBonePep R (Zhu et al, 2020).…”
Section: Discussionsupporting
confidence: 64%
“…It consists of a bovine bone-derived mineral matrix which is improved by reinforcement with the co-polymer coating poly( L -lactide-co-ε-caprolactone) (PLCL) and the addition of RGD-exposing collagen fragments from animal-derived gelatine ( D’Alessandro et al, 2017 ). During standard manufacturing process of SBN, the biomimetic peptides P2 and P6 ( Zhu et al, 2020 ) were embedded into the polymer coating of SBN, producing SmartBonePep ® (SBP) with a nominal concentration capable to provide a release rate equivalent to 1 μg/cm 3 /d over a 2 weeks time ( Figures 1A–F ) ( Perale et al, 2019 ). These two bone grafts were called SBP2 and SBP6, respectively ( Zhu et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside growth factors, synthetic peptides, inspired by intrinsically disordered proteins (IDPs) and based on proline-rich domains of enamel matrix proteins, have been shown to stimulate osteoblast differentiation in pre-osteoblastic MC3T3-E1 cells as well as in human mesenchymal stem cells [ 70 , 71 , 72 ]. These peptides were successfully and safely loaded on bone graft materials and showed enhanced in vitro bone cell responses [ 73 , 74 ]. In vivo, proline-rich peptides mimicked the effects of EMD, accelerating the wound-healing on rat oral mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…During standard manufacturing process of SBN, the biomimetic peptides P2 and P6 (Zhu et al, 2020) were embedded into the polymer coating of SBN, producing SmartBonePep R (SBP) with a nominal concentration capable to provide a release rate equivalent to 1 µg/cm 3 /d over a 2 weeks time ( Figures 1A-F) (Perale et al, 2019). These two bone grafts were called SBP2 and SBP6, respectively (Zhu et al, 2020). A third group which combine both P2 and P6 added was also added (SBP2+P6).…”
Section: Bone Graft Preparationsmentioning
confidence: 99%